MRI‐guided interventional natural killer cell delivery for liver tumor treatment. (30th March 2018) - Su, Zhanliang; Wang, Xifu; Zheng, Linfeng; Lyu, Tianchu; Figini, Matteo; Wang, Bin; Procissi, Daniel; Shangguan, Junjie; Sun, Chong; Pan, Liang; Qin, Lei; Zhang, Bin; et al.
Abstract: While natural killer (NK) cell‐based adoptive transfer immunotherapy (ATI) provides only modest clinical success in cancer patients. This study was hypothesized that MRI‐guided transcatheter intra‐hepatic arterial (IHA) infusion permits local delivery to liver tumors to improve outcomes during NK‐based ATI in a rat model of hepatocellular carcinoma (HCC). Mouse NK cells were labeled with clinically applicable iron nanocomplexes. Twenty rat HCC models were assigned to three groups: transcatheter IHA saline infusion as the control group, transcatheter IHA NK infusion group, and intravenous (IV) NK infusion group. MRI studies were performed at baseline and at 24 h, 48 h, and 8 days postinfusion. There was a significant difference in tumor R2* values between baseline and 24 h following the selective transcatheter IHA NK delivery to the tumors ( P  =   0.039) when compared to IV NK infusion ( P  =   0.803). At 8 days postinfusion, there were significant differences in tumor volumes between the control, IV, and IHA NK infusion groups (control vs. IV, P  =   0.196; control vs. IHA, P  <   0.001; and IV vs. IHA, P  =   0.001). Moreover, there was a strong correlation between tumor R2* value change (∆R2*) at 24 h postinfusion and tumor volume change (∆volume) at 8 days in IHA group ( R 2  = 0.704, P  <   0.001). Clinically applicable labeled NK cells with 12‐h labeling time can be tracked by MRI. Transcatheter IHA infusion improves NK cell homing efficacy and immunotherapeutic efficiency. The change in tumor R2* value 24 h postinfusion is an important early biomarker for prediction of longitudinal response. Abstract : Transcatheter IHA NK infusion augments NK cell homing efficiency to liver tumors. Accurate depiction of NK cell migration to tumor may permit early prediction of treatment response.